Civil-Military Relations in Maiduguri Metropolis, Borno State: A Pathway to Good Governance - Allemin Mohammed; Umar Sheriff (Walidem Institute and Publishing, 2026)
Objective: The objective of the study is to examine the civil-military relations in Maiduguri Metropolis of Borno State, Nigeria, particularly amidst the ongoing insurgency, and to identify ways in which effective civil-military relations can enhance state legitimacy, service delivery, community participation, and overall security and development. Theoretical framework: Focuses on governance, state legitimacy, and the importance of trust, coordination, and community engagement in civil-military relations. Literature review: Explores existing studies on civil-military relations in conflict zones, emphasizing challenges like trust deficits and the role of transparency and accountability. Methods: The study uses a qualitative methodology, analyzing existing literature, reports, and data on civil-military relations in Maiduguri. This likely includes interviews, case studies, and secondary data analysis to identify key themes and challenges within the civil-military context. Results: The findings reveal that effective civil-military relations contribute to improved governance, enhanced security, stability, and development in Maiduguri. Key factors for positive relations include community engagement, transparency, and accountability, which foster trust and cooperation between the military and civilians. Implications: Improved civil-military relations can enhance governance and stability in conflict zones like Maiduguri, promoting peace and development. Novelty: Focuses on Maiduguri’s specific context and offers practical recommendations for improving civil-military relations in conflict-affected regions.